Preparation of nanofiber membrane capable of adsorbing various perfluoroalkyl and polyfluoroalkyl substances
Through the preparation of quaternized chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane, the problem of low adsorption efficiency of various perfluoro and polyfluoroalkyl substances in the prior art is solved, and high-efficiency adsorption is achieved and simple operation reduces the risk of environmental pollution.
Patent Information
- Application Number
- CN202411436091.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-15
AI Technical Summary
Existing adsorption materials are difficult to efficiently adsorb and remove various perfluoro and polyfluoroalkyl substances in ambient water at the same time, especially short-chain substances, with low adsorption efficiency, and the preparation process is harsh and there is a risk of secondary pollution.
Quaternized chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane is prepared by electrospinning and chemical cross-linking of glutaraldehyde to form a nanofiber membrane with multiple adsorption mechanisms, which can simultaneously Adsorbs short- and long-chain perfluoro and polyfluoroalkyl substances.
It has achieved efficient adsorption of various types of perfluoro and polyfluoroalkyl substances, especially the adsorption efficiency of short-chain substances is increased to more than 70%, which is easy to operate and avoids secondary pollution. It is suitable for various environmental waters.
Abstract
Description
Technical Field
[0001] The invention provides a method for preparing a nanofiber membrane capable of simultaneously adsorbing and removing various types of perfluorinated and polyfluorinated alkyl substances in environmental water, belonging to the technical field of environmental water treatment. Background Art
[0002] Due to their environmental persistence, bioaccumulation, and multiple hazards to ecology and health, the prevention and control of emerging pollutants is a proposition that the world attaches great importance to. Typical persistent pollutants are emerging pollutants that are most closely related to ecological environmental safety and people's health. They have been included in the "List of New Pollutants to be Controlled (2023 Edition)" issued by the Ministry of Ecology and Environment and other six ministries and commissions, and are the first batch of emerging pollutants that must be controlled in accordance with laws and regulations. Among them, perfluorinated and polyfluoroalkyl substances are one of the emerging pollutants that are most closely related to human production and life and have the most extensive contact. They are widely used in more than 200 fields, from industrial mining to food production and firefighting foam. They are released into the environment through solid, liquid, and gaseous wastes generated in the production process, and are widely distributed in media such as air, soil, surface water, and sediments, and eventually accumulate in environmental water bodies. Environmental water is a key medium for the transportation of perfluoroalkyl and polyfluoroalkyl substances in the environment. The detection concentrations of traditional and new perfluoroalkyl substances, mainly perfluorobutyric acid, perfluorobutane sulfonic acid, perfluoropentanoic acid, perfluorohexanoic acid, perfluorohexane sulfonic acid, perfluorooctanoic acid, perfluorooctane sulfonic acid, and perfluoro(2-methyl-3-oxahexanoic acid)ammonium, range from several ng / L to millions of ng / L. Perfluoroalkyl and polyfluoroalkyl substances are extremely stable and can enter the human body through the food chain, directly affecting human health. Therefore, the adsorption and removal of perfluoroalkyl and polyfluoroalkyl substances in environmental water is one of the important propositions in the field of environmental water treatment technology.
[0003] There are many types of perfluoroalkyl and polyfluoroalkyl substances with greatly different physical and chemical properties. According to the n-octanol / water partition coefficient, they can be divided into highly polar, moderately polar and strongly hydrophobic perfluoroalkyl and polyfluoroalkyl substances, making it extremely challenging to simultaneously adsorb perfluoroalkyl and polyfluoroalkyl substances with greatly different properties. Conventional adsorbent materials such as granular activated carbon are suitable for treating long-chain perfluoroalkyl and polyfluoroalkyl substances with strong hydrophobicity, but the adsorption efficiency of short-chain perfluoroalkyl and polyfluoroalkyl substances is very low (<50%). This is because the carbon fluorine chain length of short-chain perfluoroalkyl and polyfluoroalkyl substances is not as long as that of long-chain perfluoroalkyl and polyfluoroalkyl substances, and they cannot be effectively removed by hydrophobic action. In addition, the conditions required to prepare these carbon materials are relatively harsh, and toxic / harmful solvents are used. The used granular carbon materials are not easy to separate, causing secondary pollution to the environment.
[0004] The new adsorbents developed by existing research to achieve the adsorption and removal of perfluoroalkyl substances and polyfluoroalkyl substances in environmental water include carbon materials functionalized with various functional groups (such as amino and carboxyl groups), cation-modified mineral materials, natural polymer materials (such as cellulose and β-cyclodextrin), metal organic frameworks, covalent organic frameworks and other prepared adsorbent materials. These adsorbents are often used for the adsorption and removal of a single type of perfluorocarboxylic acid, perfluorosulfonic acid, perfluoroalkyl ether carboxylic acid or perfluorononyloxybenzene sulfonate in environmental water. There are few studies on the efficient and simultaneous adsorption and removal of multiple types of perfluoroalkyl substances and polyfluoroalkyl substances in environmental water. In addition, when simultaneously adsorbing and removing multiple perfluoroalkyl substances of different polarities (different carbon chain lengths), the efficient adsorption and removal of highly polar (short-chain) perfluoroalkyl substances is a difficulty and key point. In addition, the adsorbents developed by existing research often require secondary separation processes such as centrifugation, magnetic separation and membrane filtration after the adsorption of the target substance, which reduces the ease of operation of the removal method. Therefore, considering the current status of co-contamination of multiple perfluorinated and polyfluorinated alkyl substances in environmental water, it is of great practical significance to develop efficient adsorbents to simultaneously remove multiple types of perfluorinated and polyfluorinated alkyl substances in environmental water. Summary of the invention
[0005] Technical problem: The purpose of the present invention is to prepare a method for preparing a nanofiber membrane that can adsorb multiple types of perfluorinated and polyfluoroalkyl substances, so that it can achieve simultaneous adsorption and removal of multiple types of perfluorinated and polyfluoroalkyl substance pollution.
[0006] Technical solution: The preparation method of a nanofiber membrane capable of adsorbing various types of perfluorinated and polyfluorinated alkyl substances of the present invention is achieved by the following technical solution:
[0007] S1: Preparation of quaternized chitosan;
[0008] S2: Preparation of quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane by electrospinning;
[0009] S3: The quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane is prepared by a glutaraldehyde chemical cross-linking method to obtain a quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane.
[0010] The preparation steps of the quaternized chitosan include:
[0011] S1.1: dissolving chitosan in a v / v 0.01% to 0.8% acetic acid aqueous solution to obtain a chitosan solution, wherein the concentration of chitosan is 20 to 50 g / L;
[0012] S1.2: dissolving 2,3-epoxypropyltrimethylammonium chloride in deionized water to obtain a 2,3-epoxypropyltrimethylammonium chloride solution, wherein the concentration of the 2,3-epoxypropyltrimethylammonium chloride solution is 0.60 to 1.2 g / mL;
[0013] S1.3: under the condition of heating and stirring at 60°C in a water bath, add 5% to 25% v / v 2,3-epoxypropyltrimethylammonium chloride solution dropwise to the chitosan solution prepared in step S1.1 to obtain a clear and uniform mixed solution;
[0014] S1.4: After the obtained mixed solution is centrifuged, the supernatant is taken out and poured into ethanol / acetone (v / v=1:1) and stirred slowly to produce a white gel precipitate;
[0015] S1.5: The obtained white gel precipitate is washed with anhydrous ethanol and then vacuum dried to obtain quaternized chitosan.
[0016] The steps of preparing the quaternized chitosan-polyvinyl alcohol composite nanofiber membrane by electrospinning method include:
[0017] S2.1: dissolving quaternary ammonium chitosan and polyvinyl alcohol in a v / v=20-80% acetic acid solution respectively to obtain a quaternary ammonium chitosan-polyvinyl alcohol composite solution, wherein the concentration of quaternary ammonium chitosan is 0.1-20 g / L, the concentration of polyvinyl alcohol is 80-100 g / L, and the mass ratio w / w of quaternary ammonium chitosan and polyvinyl alcohol is 5-25%;
[0018] S2.2: Place the quaternary ammonium chitosan-polyvinyl alcohol composite solution in the propeller, adjust the distance from the nozzle to the receiving screen, and prepare the quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane by electrospinning under a high-voltage electrostatic field.
[0019] The method for preparing the quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane into the quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane by the glutaraldehyde chemical cross-linking method is as follows:
[0020] Glutaraldehyde with a concentration of 0.01 to 0.05 mol / L and dilute hydrochloric acid with a concentration of 0.1 to 2 mol / L are mixed in a volume ratio of 0.5:1 to 2:1 to obtain a cross-linking solvent. After the cross-linking solvent is placed at the bottom of a closed container, a quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane is suspended in the closed container; the closed container is placed at 60 to 80° C. for 0.5 to 3 hours to obtain a quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane.
[0021] The method for removing perfluorinated and polyfluoroalkyl substances in environmental water by the nanofiber membrane is as follows: 200 to 500 mg of quaternized chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane is placed in each liter of environmental water sample to allow it to be fully immersed in the environmental water sample; after the adsorption is completed, the composite nanofiber membrane is directly removed from the environmental water sample.
[0022] The environmental water includes groundwater, surface water, tap water, domestic sewage, industrial sewage, agricultural sewage or medical wastewater.
[0023] The perfluoro and polyfluoroalkyl substances include short-chain perfluorocarboxylic acids, long-chain perfluorocarboxylic acids, short-chain perfluorosulfonic acids, long-chain perfluorosulfonic acids, perfluoroalkyl ether carboxylic acids, perfluorononyloxybenzene sulfonates, and chlorinated polyfluoroether sulfonates.
[0024] Beneficial effects: The present invention discloses a preparation method and application of a nanofiber membrane capable of adsorbing various types of perfluorinated and polyfluorinated alkyl substances, which has the following advantages and effects compared with existing adsorption materials:
[0025] (1) The quaternized chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane can adsorb a wide variety of perfluorinated and polyfluoroalkyl substances and is applicable to a wide range of sample matrices by providing a variety of adsorption mechanisms.
[0026] The prepared quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane can simultaneously adsorb perfluorinated and polyfluoroalkyl substances including short-chain perfluorocarboxylic acids, long-chain perfluorocarboxylic acids, short-chain perfluorosulfonic acids, long-chain perfluorosulfonic acids, perfluoroalkyl ether carboxylic acids, p-perfluorononyloxybenzene sulfonates and chlorinated polyfluoroether sulfonates. Compared with the existing adsorption materials, which mainly adsorb target types of traditional long-chain perfluorinated and polyfluoroalkyl substances or a few short-chain perfluorinated and polyfluoroalkyl substances, the quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane prepared by the present invention can adsorb more types of perfluorinated and polyfluoroalkyl substances.
[0027] The quaternized chitosan-polyvinyl alcohol composite nanofiber membrane can form an adsorption effect with perfluoro and polyfluoroalkyl substances through extremely strong electrostatic interaction and hydrophobic interaction. Further glutaraldehyde crosslinking enhances the hydrophobic interaction between the quaternized chitosan-polyvinyl alcohol composite nanofiber membrane and the perfluoro and polyfluoroalkyl substances, so that the adsorption efficiency of various types of perfluoro and polyfluoroalkyl substances, especially short-chain perfluoro and polyfluoroalkyl substances, can be increased to more than 70%, compared with the existing adsorption materials such as granular activated carbon and anion exchange resin for short-chain perfluoro and polyfluoroalkyl substances. The adsorption efficiency is significantly improved. That is, the electrostatic interaction provided by the quaternized chitosan and the hydrophobic interaction provided by the crosslinking of polyvinyl alcohol and glutaraldehyde constitute the adsorption mechanism of the quaternized chitosan-polyvinyl alcohol-glutaraldehyde crosslinked composite nanofiber membrane for perfluoro and polyfluoroalkyl substances, thereby achieving efficient co-adsorption of various types of perfluoro and polyfluoroalkyl substances. It is suitable for various environmental waters such as tap water, groundwater, surface water, domestic sewage, industrial sewage, agricultural sewage or medical wastewater. It only needs to be immersed in the environmental water sample, and the minimum removal rate of various types of perfluorinated and polyfluoroalkyl substances can reach more than 70% within 45 minutes.
[0028] (2) The application performance of quaternized chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane is excellent: the adsorption application method is flexible and the operation is simple.
[0029] The quaternized chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane is a "whole membrane" that can be directly immersed in environmental water to adsorb and remove perfluorinated and polyfluoroalkyl substances therein. After the adsorption and removal is completed, there is no need for secondary operations such as centrifugal filtration. Only the composite nanofiber membrane needs to be taken out from the environmental water, and solid-liquid separation can be easily completed. Compared with existing adsorption materials such as granular activated carbon, metal organic frameworks / covalent organic frameworks, magnetic materials, etc., which need to be loaded into columns or require additional steps such as high-speed centrifugation or strong magnetic field separation before use, it is not only convenient to operate, but also fundamentally avoids secondary pollution to the environment caused by the difficulty in separation.
[0030] (3) The quaternized chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane is environmentally friendly: Chitosan has good biocompatibility, biodegradability, non-toxicity, environmental friendliness, low price and easy access. The quaternary ammonium modification increases the cationicity and water solubility of chitosan. Combined with polyvinyl alcohol mixed electrospinning, it maintains the good biocompatibility and biodegradability of the nanofiber membrane, while enhancing the mechanical strength of the nanofiber membrane. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1: This example is applied to the adsorption and removal of various types of perfluorinated and polyfluorinated alkyl substances in tap water samples. The specific steps are:
[0033] S1: Preparation of chitosan as quaternized chitosan
[0034] The chitosan is dissolved in a 0.01% (v / v) acetic acid aqueous solution to obtain a chitosan solution, wherein the concentration of the chitosan is 20 g / L; 2,3-epoxypropyltrimethylammonium chloride is dissolved in deionized water to obtain a 2,3-epoxypropyltrimethylammonium chloride solution, wherein the mass concentration of the 2,3-epoxypropyltrimethylammonium chloride solution is 0.60 g / mL; under a 60° C. water bath heating and stirring condition, a 25% (v / v) 2,3-epoxypropyltrimethylammonium chloride solution is dropwise added to the chitosan solution to obtain a clear and uniform mixed solution; the obtained mixed solution is centrifuged to obtain a supernatant, and the supernatant is poured into ethanol / acetone with a v / v ratio of 1:1, and slowly stirred to generate a white gel precipitate; the obtained white gel precipitate is washed with anhydrous ethanol and then vacuum dried to obtain a quaternized chitosan.
[0035] S2: Preparation of quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane by electrospinning
[0036] Quaternary ammonium chitosan and polyvinyl alcohol are respectively dissolved in 20% (v / v) acetic acid solution to obtain a quaternary ammonium chitosan-polyvinyl alcohol composite solution, wherein the concentration of the quaternary ammonium chitosan is 6.5 g / L, the concentration of the polyvinyl alcohol is 93.5 g / L, and the mass ratio of the quaternary ammonium chitosan to the polyvinyl alcohol is 7% (w / w); the quaternary ammonium chitosan-polyvinyl alcohol composite solution is placed in a propeller, the distance from the nozzle to the receiving screen is adjusted, and the quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane is prepared by an electrostatic spinning method under a high-voltage electrostatic field.
[0037] S3: The quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane was prepared by glutaraldehyde chemical crosslinking method to obtain a quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde crosslinked composite nanofiber membrane
[0038] Glutaraldehyde with a concentration of 0.01 mol / L and dilute hydrochloric acid with a concentration of 1 mol / L are mixed in a volume ratio of 0.5:1 to obtain a cross-linking solvent. After the cross-linking solvent is placed at the bottom of a closed container, a quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane is suspended in the closed container; the closed container is placed at 60°C for 3 hours to obtain a quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane.
[0039] S4: Quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane is used as an adsorbent to adsorb and remove perfluorinated and polyfluoroalkyl substances in tap water.
[0040] The nanofiber membrane prepared by the present invention and capable of adsorbing various types of perfluorinated and polyfluoroalkyl substances in environmental water is applied to the adsorption and removal of perfluorinated and polyfluoroalkyl substances such as perfluorobutyric acid, perfluoropentanoic acid, perfluorohexanoic acid, perfluoroheptanoic acid, perfluorooctanoic acid, perfluorononanoic acid, perfluorodecanoic acid, perfluoroundecanoic acid, perfluorododecanoic acid, perfluorotridecanoic acid, perfluorobutane sulfonic acid, perfluoropentane sulfonic acid, perfluoroethane sulfonic acid, perfluoroheptane sulfonic acid, perfluorooctane sulfonic acid, perfluorononane sulfonic acid, perfluorodecane sulfonic acid, perfluorodecane sulfonic acid, perfluoro(2-methyl-3-oxahexanoic acid)ammonium, sodium p-perfluorononenyloxybenzenesulfonate and 6:2 chlorinated polyfluoroether sulfonate in tap water samples.
[0041] 200 mg of quaternized chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane is added to each liter of tap water sample, and it is fully immersed in the environmental water sample; after the adsorption is completed, the composite nanofiber membrane is directly removed from the environmental water sample. The removal efficiency can reach more than 80%.
[0042] Example 2: This example is applied to the adsorption and removal of various types of perfluorinated and polyfluorinated alkyl substances in river water samples. The specific steps are:
[0043] S1: Preparation of chitosan as quaternized chitosan
[0044] The chitosan is dissolved in a 0.8% (v / v) acetic acid aqueous solution to obtain a chitosan solution, wherein the concentration of the chitosan is 50 g / L; 2,3-epoxypropyltrimethylammonium chloride is dissolved in deionized water to obtain a 2,3-epoxypropyltrimethylammonium chloride solution, wherein the mass concentration of the 2,3-epoxypropyltrimethylammonium chloride solution is 1.2 g / mL; under a 60° C. water bath heating and stirring condition, a 5% (v / v) 2,3-epoxypropyltrimethylammonium chloride solution is dropwise added to the chitosan solution to obtain a clear and uniform mixed solution; the obtained mixed solution is centrifuged to obtain a supernatant, and the supernatant is poured into ethanol / acetone with a v / v ratio of 1:1, and slowly stirred to generate a white gel precipitate; the obtained white gel precipitate is washed with anhydrous ethanol and then vacuum dried to obtain a quaternized chitosan.
[0045] S2: Preparation of quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane by electrospinning
[0046] Quaternary ammonium chitosan and polyvinyl alcohol are respectively dissolved in 20% (v / v) acetic acid solution to obtain a quaternary ammonium chitosan-polyvinyl alcohol composite solution, wherein the concentration of the quaternary ammonium chitosan is 4.8 g / L, the concentration of the polyvinyl alcohol is 95.2 g / L, and the mass ratio of the quaternary ammonium chitosan to the polyvinyl alcohol is 5% (w / w); the quaternary ammonium chitosan-polyvinyl alcohol composite solution is placed in a propeller, the distance from the nozzle to the receiving screen is adjusted, and the quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane is prepared by an electrostatic spinning method under a high-voltage electrostatic field.
[0047] S3: The quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane was prepared by glutaraldehyde chemical crosslinking method to obtain a quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde crosslinked composite nanofiber membrane
[0048] A cross-linking solvent is obtained by mixing 0.05 mol / L glutaraldehyde and 2 mol / L dilute hydrochloric acid in a volume ratio of 2:1. The cross-linking solvent is placed at the bottom of a closed container, and then a quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane is suspended in the closed container. The closed container is placed at 80°C for 0.5 h to obtain a quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane.
[0049] S4: Quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane was used as an adsorbent to adsorb and remove per- and polyfluoroalkyl substances in river water.
[0050] The material prepared by the present invention is applied to the adsorption and removal of perfluorobutyric acid, perfluoropentanoic acid, perfluorohexanoic acid, perfluoroheptanoic acid, perfluorooctanoic acid, perfluorononanoic acid, perfluorodecanoic acid, perfluoroundecanoic acid, perfluorododecanoic acid, perfluorotridecanoic acid, perfluorobutane sulfonic acid, perfluoropentane sulfonic acid, perfluoroethane sulfonic acid, perfluoroheptane sulfonic acid, perfluorooctane sulfonic acid, perfluorononane sulfonic acid, perfluorodecane sulfonic acid, perfluorodecane sulfonic acid, perfluoro(2-methyl-3-oxahexanoic acid)ammonium, sodium p-perfluorononenyloxybenzenesulfonate and 6:2 chlorinated polyfluoroether sulfonate and other perfluoro and polyfluoroalkyl substances in river water samples.
[0051] 400 mg of quaternized chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane was added to each liter of river water sample, and it was fully immersed in the environmental water sample; after the adsorption was completed, the composite nanofiber membrane was directly removed from the environmental water sample. The removal efficiency can reach more than 75%.
[0052] Example 3: This example is applied to the adsorption and removal of various types of perfluorinated and polyfluorinated alkyl substances in lake water samples. The specific steps are:
[0053] S1: Preparation of chitosan as quaternized chitosan
[0054] The chitosan is dissolved in a 0.4% (v / v) acetic acid aqueous solution to obtain a chitosan solution, wherein the concentration of the chitosan is 30 g / L; 2,3-epoxypropyltrimethylammonium chloride is dissolved in deionized water to obtain a 2,3-epoxypropyltrimethylammonium chloride solution, wherein the mass concentration of the 2,3-epoxypropyltrimethylammonium chloride solution is 0.80 g / mL; under a 60° C. water bath heating and stirring condition, a 20% (v / v) 2,3-epoxypropyltrimethylammonium chloride solution is dropwise added to the chitosan solution to obtain a clear and uniform mixed solution; the obtained mixed solution is centrifuged to obtain a supernatant, and the supernatant is poured into ethanol / acetone with a v / v ratio of 1:1, and slowly stirred to generate a white gel precipitate; the obtained white gel precipitate is washed with anhydrous ethanol and then vacuum dried to obtain a quaternized chitosan.
[0055] S2: Preparation of quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane by electrospinning
[0056] Quaternary ammonium chitosan and polyvinyl alcohol are respectively dissolved in 40% (v / v) acetic acid solution to obtain a quaternary ammonium chitosan-polyvinyl alcohol composite solution, wherein the concentration of the quaternary ammonium chitosan is 10.7 g / L, the concentration of the polyvinyl alcohol is 89.3 g / L, and the mass ratio of the quaternary ammonium chitosan to the polyvinyl alcohol is 12% (w / w); the quaternary ammonium chitosan-polyvinyl alcohol composite solution is placed in a propeller, the distance from the nozzle to the receiving screen is adjusted, and the quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane is prepared by an electrostatic spinning method under a high-voltage electrostatic field.
[0057] S3: The quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane was prepared by glutaraldehyde chemical crosslinking method to obtain a quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde crosslinked composite nanofiber membrane
[0058] Glutaraldehyde with a concentration of 0.04 mol / L and dilute hydrochloric acid with a concentration of 1 mol / L are mixed in a volume ratio of 1:1 to obtain a cross-linking solvent. After the cross-linking solvent is placed at the bottom of a closed container, a quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane is suspended in the closed container; the closed container is placed at 65°C, and after 2.0 hours, a quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane is obtained.
[0059] S4: Using quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane as an adsorbent to remove per- and polyfluoroalkyl substances from lake water
[0060] The material prepared by the present invention is applied to the adsorption and removal of perfluorobutyric acid, perfluoropentanoic acid, perfluorohexanoic acid, perfluoroheptanoic acid, perfluorooctanoic acid, perfluorononanoic acid, perfluorodecanoic acid, perfluoroundecanoic acid, perfluorododecanoic acid, perfluorotridecanoic acid, perfluorobutane sulfonic acid, perfluoropentane sulfonic acid, perfluoroethane sulfonic acid, perfluoroheptane sulfonic acid, perfluorooctane sulfonic acid, perfluorononane sulfonic acid, perfluorodecane sulfonic acid, perfluoro(2-methyl-3-oxahexanoic acid)ammonium, sodium p-perfluorononenyloxybenzenesulfonate and 6:2 chlorinated polyfluoroether sulfonate and other perfluoro and polyfluoroalkyl substances in lake water samples.
[0061] 300 mg of quaternized chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane was added to each liter of lake water sample, and it was fully immersed in the environmental water sample; after the adsorption was completed, the composite nanofiber membrane was directly removed from the environmental water sample. The removal efficiency can reach more than 75%.
[0062] Example 4: This example is applied to the adsorption and removal of various types of perfluorinated and polyfluorinated alkyl substances in industrial wastewater samples. The specific steps are as follows:
[0063] S1: Preparation of chitosan as quaternized chitosan
[0064] The chitosan is dissolved in a 0.5% (v / v) acetic acid aqueous solution to obtain a chitosan solution, wherein the concentration of the chitosan is 25 g / L; 2,3-epoxypropyltrimethylammonium chloride is dissolved in deionized water to obtain a 2,3-epoxypropyltrimethylammonium chloride solution, wherein the mass concentration of the 2,3-epoxypropyltrimethylammonium chloride solution is 0.70 g / mL; under a 60° C. water bath heating and stirring condition, a 15% (v / v) 2,3-epoxypropyltrimethylammonium chloride solution is dropwise added to the chitosan solution to obtain a clear and uniform mixed solution; the obtained mixed solution is centrifuged to obtain a supernatant, and the supernatant is poured into ethanol / acetone with a v / v ratio of 1:1, and slowly stirred to generate a white gel precipitate; the obtained white gel precipitate is washed with anhydrous ethanol and then vacuum dried to obtain a quaternized chitosan.
[0065] S2: Preparation of quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane by electrospinning
[0066] Quaternary ammonium chitosan and polyvinyl alcohol are respectively dissolved in 80% (v / v) acetic acid solution to obtain a quaternary ammonium chitosan-polyvinyl alcohol composite solution, wherein the concentration of the quaternary ammonium chitosan is 20 g / L, the concentration of the polyvinyl alcohol is 80 g / L, and the mass ratio of the quaternary ammonium chitosan to the polyvinyl alcohol is 25% (w / w); the quaternary ammonium chitosan-polyvinyl alcohol composite solution is placed in a propeller, the distance from the nozzle to the receiving screen is adjusted, and the quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane is prepared by an electrostatic spinning method under a high-voltage electrostatic field.
[0067] S3: The quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane was prepared by glutaraldehyde chemical crosslinking method to obtain a quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde crosslinked composite nanofiber membrane
[0068] A cross-linking solvent is obtained by mixing 0.05 mol / L glutaraldehyde and 1.5 mol / L dilute hydrochloric acid in a volume ratio of 1.5:1. The cross-linking solvent is placed at the bottom of a closed container, and then the quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane is suspended in the closed container. The closed container is placed at 75°C for 1.0 h to obtain a quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane.
[0069] S4: Using quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane as an adsorbent to remove per- and polyfluoroalkyl substances from industrial wastewater
[0070] The material prepared by the present invention is applied to the adsorption and removal of perfluorobutyric acid, perfluoropentanoic acid, perfluorohexanoic acid, perfluoroheptanoic acid, perfluorooctanoic acid, perfluorononanoic acid, perfluorodecanoic acid, perfluoroundecanoic acid, perfluorododecanoic acid, perfluorotridecanoic acid, perfluorobutane sulfonic acid, perfluoropentane sulfonic acid, perfluoroethane sulfonic acid, perfluoroheptane sulfonic acid, perfluorooctane sulfonic acid, perfluorononane sulfonic acid, perfluorodecane sulfonic acid, perfluoro(2-methyl-3-oxahexanoic acid)ammonium, sodium p-perfluorononenyloxybenzenesulfonate and 6:2 chlorinated polyfluoroether sulfonate and other perfluoro and polyfluoroalkyl substances in industrial wastewater samples.
[0071] 500 mg of quaternized chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane is added to each liter of industrial wastewater sample, and it is fully immersed in the environmental water sample; after the adsorption is completed, the composite nanofiber membrane is directly taken out from the environmental water sample. The removal efficiency can reach more than 70%.
[0072] Example 5: This example is applied to the adsorption and removal of various types of perfluorinated and polyfluoroalkyl substances in domestic sewage samples. The specific steps are as follows:
[0073] S1: Preparation of chitosan as quaternized chitosan
[0074] The chitosan is dissolved in a 0.65% (v / v) acetic acid aqueous solution to obtain a chitosan solution, wherein the concentration of the chitosan is 35 g / L; 2,3-epoxypropyltrimethylammonium chloride is dissolved in deionized water to obtain a 2,3-epoxypropyltrimethylammonium chloride solution, wherein the mass concentration of the 2,3-epoxypropyltrimethylammonium chloride solution is 1.0 g / mL; under a 60° C. water bath heating and stirring condition, a 10% (v / v) 2,3-epoxypropyltrimethylammonium chloride solution is dropwise added to the chitosan solution to obtain a clear and uniform mixed solution; the obtained mixed solution is centrifuged to obtain a supernatant, and the supernatant is poured into ethanol / acetone with a v / v ratio of 1:1, and slowly stirred to generate a white gel precipitate; the obtained white gel precipitate is washed with anhydrous ethanol and then vacuum dried to obtain a quaternized chitosan.
[0075] S2: Preparation of quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane by electrospinning
[0076] Quaternary ammonium chitosan and polyvinyl alcohol are respectively dissolved in 60% (v / v) acetic acid solution to obtain a quaternary ammonium chitosan-polyvinyl alcohol composite solution, wherein the concentration of the quaternary ammonium chitosan is 15.3 g / L, the concentration of the polyvinyl alcohol is 84.7 g / L, and the mass ratio of the quaternary ammonium chitosan to the polyvinyl alcohol is 18% (w / w); the quaternary ammonium chitosan-polyvinyl alcohol composite solution is placed in a propeller, the distance from the nozzle to the receiving screen is adjusted, and the quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane is prepared by an electrostatic spinning method under a high-voltage electrostatic field.
[0077] S3: The quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane was prepared by glutaraldehyde chemical crosslinking method to obtain a quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde crosslinked composite nanofiber membrane
[0078] A cross-linking solvent is obtained by mixing 0.05 mol / L glutaraldehyde and 1.5 mol / L dilute hydrochloric acid in a volume ratio of 0.5:1. The cross-linking solvent is placed at the bottom of a closed container, and then the quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane is suspended in the closed container. The closed container is placed at 70°C for 0.5 h to obtain a quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane.
[0079] S4: Using quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane as an adsorbent to remove per- and polyfluoroalkyl substances from domestic sewage
[0080] The material prepared by the present invention is applied to the adsorption and removal of perfluorobutyric acid, perfluoropentanoic acid, perfluorohexanoic acid, perfluoroheptanoic acid, perfluorooctanoic acid, perfluorononanoic acid, perfluorodecanoic acid, perfluoroundecanoic acid, perfluorododecanoic acid, perfluorotridecanoic acid, perfluorobutane sulfonic acid, perfluoropentane sulfonic acid, perfluoroethane sulfonic acid, perfluoroheptane sulfonic acid, perfluorooctane sulfonic acid, perfluorononane sulfonic acid, perfluorodecane sulfonic acid, perfluoro(2-methyl-3-oxahexanoic acid)ammonium, sodium p-perfluorononenyloxybenzenesulfonate and 6:2 chlorinated polyfluoroether sulfonate and other perfluoro and polyfluoroalkyl substances in domestic sewage samples.
[0081] 300 mg of quaternized chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane was added to each liter of domestic sewage sample, and it was fully immersed in the environmental water sample; after the adsorption was completed, the composite nanofiber membrane was directly removed from the environmental water sample. The removal efficiency can reach more than 72%.
[0082] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0083] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A method for preparing a nanofiber membrane capable of adsorbing multiple types of perfluoroalkyl and polyfluoroalkyl substances, characterized in that: Prepared by the following steps: S1: Preparation of quaternized chitosan; S2: Preparation of quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane by electrospinning; S3: The quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane is prepared by a glutaraldehyde chemical cross-linking method to obtain a quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane.
2. The method for preparing a nanofiber membrane capable of adsorbing multiple types of perfluoroalkyl and polyfluoroalkyl substances according to claim 1, characterized in that: The preparation steps of the quaternized chitosan include: S1.1: dissolving chitosan in a v / v 0.01% to 0.8% acetic acid aqueous solution to obtain a chitosan solution, wherein the concentration of chitosan is 20 to 50 g / L; S1.2: dissolving 2,3-epoxypropyltrimethylammonium chloride in deionized water to obtain a 2,3-epoxypropyltrimethylammonium chloride solution, wherein the concentration of the 2,3-epoxypropyltrimethylammonium chloride solution is 0.60 to 1.2 g / mL; S1.3: under the condition of heating and stirring at 60°C in a water bath, add 5% to 25% v / v 2,3-epoxypropyltrimethylammonium chloride solution dropwise to the chitosan solution prepared in step S1.1 to obtain a clear and uniform mixed solution; S1.4: After the obtained mixed solution is centrifuged, the supernatant is taken out and poured into ethanol / acetone (v / v=1:1) and stirred slowly to produce a white gel precipitate; S1.5: The obtained white gel precipitate is washed with anhydrous ethanol and then vacuum dried to obtain quaternized chitosan.
3. The method for preparing a nanofiber membrane capable of adsorbing multiple types of perfluoroalkyl and polyfluoroalkyl substances according to claim 1, characterized in that: The steps of preparing the quaternized chitosan-polyvinyl alcohol composite nanofiber membrane by electrospinning method include: S2.1: dissolving quaternary ammonium chitosan and polyvinyl alcohol in a v / v=20-80% acetic acid solution respectively to obtain a quaternary ammonium chitosan-polyvinyl alcohol composite solution, wherein the concentration of quaternary ammonium chitosan is 0.1-20 g / L, the concentration of polyvinyl alcohol is 80-100 g / L, and the mass ratio w / w of quaternary ammonium chitosan and polyvinyl alcohol is 5-25%; S2.2: Place the quaternary ammonium chitosan-polyvinyl alcohol composite solution in the propeller, adjust the distance from the nozzle to the receiving screen, and prepare the quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane by electrospinning under a high-voltage electrostatic field.
4. The method for preparing a nanofiber membrane capable of adsorbing multiple types of perfluoroalkyl and polyfluoroalkyl substances according to claim 1, characterized in that: The method for preparing the quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane into the quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane by the glutaraldehyde chemical cross-linking method is as follows: Glutaraldehyde with a concentration of 0.01 to 0.05 mol / L and dilute hydrochloric acid with a concentration of 0.1 to 2 mol / L are mixed in a volume ratio of 0.5:1 to 2:1 to obtain a cross-linking solvent. After the cross-linking solvent is placed at the bottom of a closed container, a quaternary ammonium chitosan-polyvinyl alcohol composite nanofiber membrane is suspended in the closed container; the closed container is placed at 60 to 80° C. for 0.5 to 3 hours to obtain a quaternary ammonium chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane.
5. A method for adsorbing multiple types of perfluoroalkyl and polyfluoroalkyl substances in environmental water by a nanofiber membrane obtained as claimed in claim 1, 2, 3 or 4, characterized in that: The method for removing perfluorinated and polyfluoroalkyl substances in environmental water by the nanofiber membrane is as follows: 200 to 500 mg of quaternized chitosan-polyvinyl alcohol-glutaraldehyde cross-linked composite nanofiber membrane is placed in each liter of environmental water sample to allow it to be fully immersed in the environmental water sample; after the adsorption is completed, the composite nanofiber membrane is directly removed from the environmental water sample.
6. The method for adsorbing multiple types of perfluoroalkyl and polyfluoroalkyl substances in environmental water by nanofiber membrane according to claim 5, characterized in that: The environmental water includes groundwater, surface water, tap water, domestic sewage, industrial sewage, agricultural sewage or medical wastewater.
7. The method for adsorbing multiple types of perfluoroalkyl and polyfluoroalkyl substances in environmental water by nanofiber membrane according to claim 5, characterized in that: The perfluoro and polyfluoroalkyl substances include short-chain perfluorocarboxylic acids, long-chain perfluorocarboxylic acids, short-chain perfluorosulfonic acids, long-chain perfluorosulfonic acids, perfluoroalkyl ether carboxylic acids, perfluorononyloxybenzene sulfonates, and chlorinated polyfluoroether sulfonates.
Citation Information
Patent Citations
Preparation method of chitosan-based drug-loading composite antibacterial superfine fiber membrane
CN103933602A
Preparation method of quaternized polyvinyl alcohol / chitosan electrospinning solid electrolyte film
CN108823983A
Method for preparing quaternary ammonium salt chitosan and polyvinyl alcohol antibacterial filter composite material
CN109316824A
Preparation method of nanofiber oil-water separation membrane, and nanofiber oil-water separation membrane
CN113663533A
Chitosan-based electrostatic spinning fiber membrane capable of efficiently recovering gold element in water body
CN115554864A
Cited By
Bio-based antibacterial cool-feeling breathable film and preparation method thereof
CN120682613A
Adsorption flowing water driven friction catalysis pipeline water quality purification device as well as preparation method and application thereof
CN120943388A